Top-class women`s soccer performance: peak demands and distribution of the match activities relative to maximal intensities during official matches - Riboli, A.; Francini, L.; Rossi, E.; Caronti, A.; Boldrini, L.; Mazzoni, S. (Biology of Sport, 2024)
The aims of the current study were to determine the most demanding passages of match play (MDP) and the distribution of match activities relative to maximum intensities during official matches in top-class women soccer players. Twenty-eight women players competing in European championship and international UEFA competitions were monitored during 38 official matches (277 individual samples). Maximum relative (m · min-1) total distance (TD), high-speed running (HSRD), very high-speed running (VHSRD), sprint, acceleration and deceleration distances were calculated across different durations (1-5, 10, 15, 90 min) using a rolling average analysis. Maximum intensities (1-minpeak) were used as the reference value to determine the distribution of relative intensity across the whole-match demands (90-minavg). Time and distance higher than 90-minavg (> 90-minavg) were also calculated. MDP showed moderate to very large [effect size (ES): 0.63/5.20] differences between 1-minpeak vs all durations for each parameter. The relative (m · min-1) 1-minpeak was greater than 90-minavg of about +63% for TD, +358% for HSRD, +969% for VHSRD, +2785% for sprint, +1216% for acceleration, and +768% for deceleration. The total distance covered > 90-minavg was ~66.6% of the total distance covered during the 90-minavg for TD, ~84.8% for HSRD, ~97.4% for VHSRD, ~100% for sprint, ~99.1% for acceleration and ~98.2% for deceleration. The relative distance > 90-minavg was higher (P < 0.05) than the 90-minavg for each metric (ES: 2.22 to 7.58; very large). The present results may help coaches and sport scientists to replicate the peak demands during training routine in top-class women soccer players.